Characterization of acetylated and acetolyzed glycoprotein high-mannose core oligosaccharides by fast-atom-bombardment mass spectrometry. - Tsai, P K (1986)
Fast-atom-bombardment mass spectrometry has been applied to acetylated neutral and phosphorylated oligosaccharides from yeast glycoproteins and to their acetolysis products. Although acetylation increases the sample molecular weight and the complexity of the spectra, it also enhances the sensitivity of detection, is applicable to samples that contain salt, and is especially useful for analysis of phosphorylated derivatives. Acetylation by trifluoroacetic anhydride/glacial acetic acid is particularly convenient and can be done rapidly on a small amount of material. Acetolysis by acetic anhydride/glacial acetic acid/H2SO4 is done on the acetylated oligosaccharides, and the acetylated fragments are recovered by solvent extraction and immediately subjected to mass spectrometry. The methodology allows molecular weight determinations and sequence analysis by acetolysis to be carried out on a few micrograms of isolated oligosaccharide in a few hours.